(untitled) (Contemporary Journal of Social Science Review, 2025)
This research paper was performed to investigate the causes of political instability in Pakistan and its subsequent impacts on foreign policy of the country. This paper also attempts to discuss how military, and their actions affect the democratic culture in the state. The researcher has evaluated the roles and responsibilities of the political parties in Pakistan by examining their different functions, which include the responsibility to strengthen the internal stability and foreign policy. The internal politics in Pakistan has always been keen in shaping the foreign policy of the country with the engagement of different stake holders. The data were collected by researching mainly using secondary sources that discussed and evaluated the objectives of the thesis. Further, a content analysis method was used to analyze the data and characterize the contributions of different factors in shaping the political culture of Pakistan and their effects on the democratic system of Pakistan.